Improving Community Literacy in Environmental Management Through Community-Based Education in Muara Kaman District, Kutai Kartanegara District, East Kalimantan Provision - Suhardi Suhardi; Dede Aprylasari; Ari Wibowo (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
Increasing community literacy in environmental management is a strategic step to realize sustainable development. One practical approach that can be implemented is through community-based education. This article examines how local communities can become agents of change in increasing public awareness and understanding regarding environmental issues, such as waste management, natural resource conservation, and adaptation to climate change. Through a participatory approach, community-based education encourages direct community involvement in designing and implementing environmental programs that suit local needs. Case studies from various regions show that collaboration between communities, government, and the private sector can increase the effectiveness of educational programs and create long-term impacts. The work programs are processing organic and inorganic waste, processing agricultural land, planting trees, preventing dengue fever and making anti-mosquito spray, providing information related to Hoaxes and phishing link modes, and collecting data on MSMEs. Apart from that, there are also work programs regarding learning posts, introducing waste banks, making street signs, and creating village websites. The results obtained from this activity are an approach to the community through social activities carried out with residents and increasing community insight through the outreach and training programs provided. Apart from that, village facilities can be improved by creating street signs and village websites. It is hoped that the results of this study can become a practical guide in developing a sustainable community-based education model for environmental management.